Polygamy: A Threat or Opportunity to The Islamic Family? (Sociology and Family Law Perspectives) - Ritonga, Denna; B. Syafuri; Faisal Zulfikar; Tarihoran, Nafan; Jambunanda, Ahmad Jamaludin; Karimuddin, Karimuddin (Nurani: jurnal kajian syari’ah dan masyarakat, 2025)
This study examines societal perspectives and actual practices related to polygamy within the framework of Islamic teachings. The aim is to understand how polygamy is perceived and practiced in contemporary Muslim communities, as well as the gap between the ideal concept of polygamy in Islam and its reality in social life. The study used a mixed approach, combining analysis of primary data obtained from in-depth interviews with polygamous families of community leaders, academics, and legal practitioners, with a comprehensive literature review. The study's findings reveal a considerable diversity in societal perceptions regarding polygamy. Factors such as education level, religious understanding, and personal experience influence the acceptance of this practice. This study identifies that discussions about polygamy in Indonesia are often problematic with endless pros and cons views. Many wives reject polygamy because they feel that they are victims of their husbands' injustice, with cases of neglect of children of polygamous victims becoming increasingly unsettling. The Indonesian Child Protection Commission even recorded an increase in complaints related to child neglect in the context of polygamous families. Research shows that in practice, polygamy often brings disadvantages, especially for wives and children. This research underscores the importance of conducting a comparative analysis between normative ideals and actual practices, employing a multidimensional framework that integrates legal, social, and psychological perspectives. It also emphasizes the relevance of formulating policy responses to effectively address the emerging issues.